Carbon nanotube-based materials for lithium-sulfur batteries - Zheng, Mingbo; Chi, Yao; Hu, Qin; Tang, Hao; Jiang, Xinliang; Zhang, Li; Zhang, Songtao; Pang, Huan; Xu, Qiang (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
Lithium-sulfur batteries (Li-S) have attracted considerable attention because of their high theoretical energy density (2600 W h kg −1 ). However, practical commercial applications of Li-S batteries are limited by the low conductivity of sulfur and discharge products, severe polysulfide shuttling effect, and large sulfur volume expansion during discharge. Various nanostructured carbon materials have been used as sulfur host materials to overcome these problems. Carbon nanotubes (CNTs) are superior to other nanostructured carbon materials because of their unique 1D nanostructure, good conductivity, excellent flexibility, and stable chemical properties. This article reviews the application of CNT-based materials, including simple CNT materials and CNT-based nanocomposites, in Li-S batteries and the particular roles of CNTs in this system. First, general information about the function of CNTs in Li-S batteries and the preparation method of CNT/sulfur composite is provided. Second, various simple CNTs are described, and their inherent characteristics are discussed. Third, CNT-based nanocomposites, including carbon material@CNTs, chemisorption host material@CNTs, and nanocomposites based on in situ formed CNTs, are summarized. The synergistic effect of components and the function of CNTs in the composite are discussed specifically. Fourth, further treatments for CNT/S nanocomposites to better control the diffusion of polysulfides are summarized. Finally, future directions and prospects are discussed. Research progress in the application of carbon nanotube-based materials in lithium-sulfur batteries is summarized and evaluated.